The influence of part-whole method and video analysis media on long jump learning outcomes - Jaya Saputra; Sri Gusti Handayani; Aldo Naza Putra; Zulbahri Zulbahri (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study aimed to examine the effect of the combination of the Part-Whole Method and Video Analysis Media on cognitive learning outcomes and psychomotor skills in long jump learning among junior high school students. This study employed a quasi-experimental design using a pre-test and post-test control group approach involving 56 seventh-grade students of SMP Negeri 02 Kabawetan who were divided equally into an experimental group (n = 28) and a control group (n = 28). The intervention was conducted over eight instructional meetings. Cognitive learning outcomes were measured using a written test based on revised Bloom’s Taxonomy, while psychomotor skills were assessed using a performance rubric and jump distance measurements. Data were analyzed using descriptive statistics, N-Gain analysis, paired sample t-tests, and independent sample t-tests. The results showed that the experimental group achieved significantly higher cognitive post-test scores (84.36 ± 5.18) and psychomotor post-test scores (87.25 ± 4.67) compared to the control group, with significant differences (p < 0.001) and very large effect sizes (d = 1.84; d = 1.97). The integration of both methods effectively improved students’ long jump learning outcomes.